Reducing Islamophobia Through The Reconstruction of Sunan Ampel’s Work on IRD Batik Motif Pegon - Indriya Rusmana; Zahrotunnimah Zahrotunnimah (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
The term Islamophobia is defined as prejudice, inclination towards hatred, and also a form of cultural racism. A study conducted by Henk Dekker and Jolanda van der Noll entitled 'Islamophobia and Its Origins: A Study Among Dutch Youth' to 580 adolescents in the Netherlands in 2006, has confirmed that 54% of the respondents had negative views about Islam and Muslims. Walisongo was known as a propagator of Islam in the land of Java, the intellectuals and reformers of Javanese society at the beginning of the 17th century. From the nine people of Walisongo, Sunan Ampel was the one who was known as the creator of Pegon Jawa letters, which was used as a medium in transforming knowledge and Islamic teachings to be better understood by the society at that time. Until now Pegon Jawa letters are still being used in Islamic boarding schools and madrassas, be it in Indonesia, Malaysia, and Thailand. Islamic education is many efforts in educating Islam in a planned manner through various experiences, knowledge, capabilities and skills so that students can recognize, understand, appreciate, and believe in Islamic teachings. Batik is a legacy of wastra art (traditional cloth) that has many stories and high philosophical value in each of its strands. Batik is a cultural achievement, world cultural heritage, that has to be preserved and developed. This research is conducted using qualitative approach, with an effort to describe the reconstruction of the teachings of Sunan Ampel in batik motif Pegon Jawa. Collecting data is conducted through observation, literature studies, interviews, and documentation, and analyzed descriptively. There are three results that come up from this study. First, the reconstruction of the teachings of Sunan Ampel into batik motif Pegon Jawa, secondly, Pegon Jawa letters as an educational media and Islamic cultural art, and third, scientifical social implementation of batik motif Pegon Jawa as an effort to ward off Islamophobia.